Streptococcus suis meningitis related to processing and consuming raw pork during Balinese tradition, Mebat (Medical Journal of Indonesia, 2020)
Streptococcus suis is a zoonotic pathogen that can infect humans, especially meningitis. S. suis meningitis has been commonly diagnosed in Bali, which is associated with the consumption of raw pork. We reported case of S. suis meningitis that could have occurred due to the ingestion of undercooked pork during a traditional ceremony, which also involved two more patients with similar symptoms. A 62-year-old male was brought to the emergency unit because of decreased consciousness (Glasgow coma scale 14/15) in the last 8 hours before admission. He also had a headache, high fever, and stiff neck. Examination of cerebrospinal fluid revealed the presence of S. suis infection and was confirmed by polymerase chain reaction. The patient was administered ceftriaxone and showed a clinical improvement on the third day without any hearing problem.